Efektywność projektów inwestycyjnych a ryzyko - Wiśniewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Capital investment appraisal methods should incorporate risk in the analysis. Risk is taken into account through increase of discount rate or analysis of outcomes in relation to changes in input parameters. The former method is appropriate for market risk only which cannot be diversified away by the investors (owners). The latter one is appropriate for analysis of impact of total risk on the investment results including specific risk of the project. Especially the latter method of risk analysis is not frequently used by Polish firms. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 619-628